Analysis of Key Parameters Affecting the Performance of Solar-Driven Electrolysis (Journal of Technology Research, 2025)
As the world seeks sustainable and environmentally friendly energy solutions, hydrogen has emerged as a promising alternative to traditional fossil fuels. Harnessing renewable energy sources, especially solar energy, offers a clean method for hydrogen production that can be used in various sectors. This study explores the design and performance of a solar-powered electrochemical system for hydrogen production via water electrolysis. The research investigates the impact of key operational parameters, including electrolyte pH, electrode surface area, and sunlight incidence angle, on hydrogen yield and system efficiency. Utilizing a conventional alkaline electrolyze coupled with monocrystalline solar panels at varying angles, experiments demonstrate that alkaline conditions (pH 9) and increased electrode surface area significantly enhance hydrogen generation. Among the tested angles, 45° provided optimal solar radiation absorption, resulting in higher hydrogen output. Comparative analysis indicates that while traditional power sources offer greater stability, solar-driven systems present a promising, environmentally friendly alternative for sustainable hydrogen production. The findings suggest potential improvements through advanced electrode materials, solar tracking, and system optimization for real world applications, emphasizing the role of renewable energy in advancing clean hydrogen technologies.
Keywords: Solar energy conversion; Hydrogen production; Water electrolysis; Renewable energy; Sustainable fuel